A cultura otaku no Brasil: da obsessão à criação de um Japão imaginado - Santos, André Noro dos (2017)
The objective of this thesis is to analyze the behavior of the Brazilian otakus and how they imagine and translate their obsession with the Japanese culture. As an empirical object we chose the manga created by Brazilians and some otaku communities reunited in social networks and pop culture events. The hypothesis is that in the translation of the otaku culture and its media products, rather than a language search that could generate, for example, a "mongrel manga", is the mimesis and the assimilation of a behavior and a way of life which, in the Brazilian version, becomes quite unique and, not rarely, distant from some stereotypes generated by the Japanese themselves. In this regard, we observe that the Brazilian otakus have nothing to do with the image of the introspective otakus that marked the beginning of the movement in Japan. The theoretical fundation was based on foreign (e.g. Azuma and LaMarre) and Brazilian (e.g. Luyten, Nunes and Almeida) bibliographies that analyzed the phenomenon. In methodological terms, the research was also extended to the social networks, which constitute the major means of communication of the otakus, as well as to places of concentration of these groups such as the Liberdade neighborhood in São Paulo. The results indicate that the Brazilian otaku culture was gradually becoming another way of commercializing an imagined Japan (Greiner 2015 and 2017), differing from other experiences by focusing exclusively on Japanese culture, without adopting a generic Asian image